Perancangan E-Commerce pada PT DAF - Rudy Rudy; George Aryanto Abraham; Ryan M A; Yohanna Yohanna (Bina Nusantara University, 2010)
The purpose of this study is to analyze and design e-commerce at. DAF to help the sales process is then expected to improve service. The methodology used is the method of analysis, where the review is held directly to the field, observing and analyzing the data obtained, and using the design method, which includes design of business models, screen designs and database design. Results to be achieved is the application of e-commerce web-based, whereby the system can enable customers to obtain the desired information is complete, make transactions easier and faster. Conclusions obtained are PT DAF can take advantage of e-commerce to support their business today and an appropriate business model is the highest-quality models.